Predoctoral publications and academic career: a systematic review and future directions - Mertkan, Sefika; Takir, Aygil; Shamsi, Ahmad Fawzi; Osam, Ulker Vanci (Routledge Journals, Taylor & Francis Ltd, 2025)
Publishing prior to completing graduate school is increasingly institutionalised through institutional policies in ways that pressurise doctoral students to publish as a graduation requirement or encourage them to do so to gain advantages in the academic job market. However, no systematic review of the role predoctoral publications play in shaping future career has been undertaken to date. This paper summarises and synthesises findings from studies examining the association between predoctoral publications and career outcomes while also outlining a research agenda to increase our understanding of how predoctoral publications influence scholars' future career.
Keywords: Academic publishing; Academic career; Doctoral students